Recent progress on supercapacitive performance of agrowaste fibers: a review. Issue 2 (4th March 2023) - Subramaniam, Thilageshwaran; Krishnan, Syam G.; Ansari, M. N. M.; Hamid, Nasri A; Khalid, Mohammad
Abstract: The waste-to-wealth practice has evolved into the circular economy concept, in which every by-product is converted into a usable product, enabling the concept of zero-waste. As a result, research on converting wastes, particularly bio and agricultural wastes, into usable products is prioritized. Activated carbons are one of these products, which are derived through a variety of physical and chemical processes from agricultural and biowaste. These activated carbons have applications in various fields, including energy storage, catalysis, and water purification. However, the quality of this activated carbon is dependent on the bioresource's structure and chemical composition. As a result, many sources to produce activated carbon, including stems, wood, leaves, root, bark, fiber, flower, and seeds, have been identified and are being explored for their potential use as an electrode material for supercapacitors. Out of these sources, fiber from different bioresources shows improved performance as supercapacitor electrodes due to their higher cellulose and lignin contents. In this study, we systematically review various sources of activated carbon and their performance as supercapacitor electrodes. The electrochemical characterization methodologies used to characterize this fiber-based activated carbon are examined critically, and factors influencing its improved/poor performance are collated. Additionally, the most performing fiber-based sources of activated carbon for supercapacitor electrodes are identified, along with a future perspective.